2003
DOI: 10.1291/hypres.26.369
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Hormone Replacement Therapy on Office and Ambulatory Blood Pressure in Japanese Hypertensive Postmenopausal Women

Abstract: in postmenopausal women are poorly understood. HRT has been reported to decrease (6-16) or not to change (17-25) BP in normotensive and hypertensive postmenopausal women. The lack of an effect might be dependent on the type, dose, and route of estrogen and progesterone used as well as the methods used for the measurement of BP.HRT has been considered relatively contraindicated for patients with hypertension. This stems from the observed hypertensive effects of oral contraceptives, documented in the 1970s (26,2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 51 publications
0
11
0
Order By: Relevance
“…Moreover, oestradiol did not affect either systolic or diastolic blood pressure, supporting previous work showing that HRT may not be harmful in hypertensive postmenopausal women. 24 The role of HRT in diastolic dysfunction remains unclear. Recent studies have shown conflicting results, but these discrepancies may be explained by differences in methodology, biological variables, and the types of hormone preparations used.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, oestradiol did not affect either systolic or diastolic blood pressure, supporting previous work showing that HRT may not be harmful in hypertensive postmenopausal women. 24 The role of HRT in diastolic dysfunction remains unclear. Recent studies have shown conflicting results, but these discrepancies may be explained by differences in methodology, biological variables, and the types of hormone preparations used.…”
Section: Discussionmentioning
confidence: 99%
“…The notion that the prevalence of hypertension and cardiovascular disease differ between men and women is well established, being women protected from cardiovascular events until menopause, with a rapid increase in their risk profile beyond that age [11][12][13]. Responsibility for the observed differences has been attributed to sex hormones, although hormone replacement therapy failed to decrease coronary events in post-menopausal women and had negligible effect on blood pressure [14][15][16][17]. Gene-specific effects have been indicated as responsible, but most of genetic studies did not include sex as a variable in data analysis and a recent meta-analysis pooling thousands of subjects of previous GWASs did not identify any sex-specific effect of genes associated to blood pressure/hypertension [18].…”
Section: Introductionmentioning
confidence: 99%
“…In studies using ABPM in hypertensive women, oral and transdermal HT showed a neutral or decreasing effect on BP [2][3][4][5][6]. Most of the studies that showed a decreasing effect on BP used standard doses or even high doses of estrogens [27].…”
Section: Discussionmentioning
confidence: 99%
“…The data about the effects of HT in hypertensive menopausal women are discordant [2][3][4][5][6]. These studies differ in some aspects such as route of administration, dose, and type of estrogen and progestogen used.…”
Section: Introductionmentioning
confidence: 99%